Energy and the food system - Woods, Jeremy; Williams, Adrian G.; Hughes, John K.; Black, Mairi; Murphy, Richard (Royal Society, 2010)
Modern agriculture is heavily dependent on fossil resources. Both direct energy use for crop management and indirect energy use for fertilizers, pesticides and machinery production have contributed to the major increases in food production seen since the 1960s. However, the relationship between energy inputs and yields is not linear. Low-energy inputs can lead to lower yields and perversely to higher energy demands per tonne of harvested product. At the other extreme, increasing energy inputs can lead to ever-smaller yield gains. Although fossil fuels remain the dominant source of energy for agriculture, the mix of fuels used differs owing to the different fertilization and cultivation requirements of individual crops. Nitrogen fertilizer production uses large amounts of natural gas and some coal, and can account for more than 50 per cent of total energy use in commercial agriculture. Oil accounts for between 30 and 75 per cent of energy inputs of UK agriculture, depending on the cropping system. While agriculture remains dependent on fossil sources of energy, food prices will couple to fossil energy prices and food production will remain a significant contributor to anthropogenic greenhouse gas emissions. Technological developments, changes in crop management, and renewable energy will all play important roles in increasing the energy efficiency of agriculture and reducing its reliance of fossil resources. Keywords: energy in agriculture; fossil energy; agricultural greenhouse gas emissions; land use; agroforestry; policy